The next Multiannual Financial Framework and the strategic challenges and risks to the European Union's fundamental objectives and values - Dencho Georgiev (CES Working Papers, 2019)
The central challenge for the Union's future is the overcoming of economic, social and territorial inequalities among its Member States. With the next MFF, there is an opportunity to make the Union's system of 'own resources' less regressive and more equitable. Progressivity in the financing of EU policies with redistributive effects could be introduced by combining progressive coefficients, national co-financing, and other automatic progressive stabilizers. This would ensure that solidarity becomes a matter of the rule of law and not of governance through conditionalities and fines. Unless the EU undertakes an effective reform of the financing of its redistributive policies to ensure that progressivity and solidarity in the EU become a matter of the rule of law, the Union will bear less and less resemblance to a democracy and will increasingly look like an empire with an economically stronger and more rapidly developing 'core' and an economically weaker 'periphery' in the East and the South, lagging behind the 'core'.
Keywords: 330; Multiannual Financial Framework; EU solidarity; rule of law; cohesion policy; progressivity